2021
DOI: 10.1002/ijfe.2420
|View full text |Cite
|
Sign up to set email alerts
|

The role of corporate governance in attracting foreign investment: An empirical investigation of Saudi‐listed firms in light of vision 2030

Abstract: Following the introduction of the Saudi Vision 2030, diverse developments have been considered concerning corporate governance as an effort to open Saudi Arabia's economy to the world. Identifying the significance of attracting foreign investment is considered an approach to accomplish one of the vision's targets. The objective of this study is to investigate the impact of improved corporate governance policies on the magnitude of foreign investment. Regression analysis was employed using the data of 153 liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Third, in 2016, Saudi Arabia embarked on a plan (Saudi Vision 2030) to diversify its economy beyond oil. In an effort to attract more foreign investment and intensify the privatization of state-run companies, the government has greenlighted the appointment of foreigners at the head of state-run companies [20,21]. Therefore, the role of foreign CEO towards firm CSR disclosure policy in Saudi Arabia is an empirical issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, in 2016, Saudi Arabia embarked on a plan (Saudi Vision 2030) to diversify its economy beyond oil. In an effort to attract more foreign investment and intensify the privatization of state-run companies, the government has greenlighted the appointment of foreigners at the head of state-run companies [20,21]. Therefore, the role of foreign CEO towards firm CSR disclosure policy in Saudi Arabia is an empirical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Third, in 2016, Saudi Arabia embarked on a plan (Saudi Vision 2030) economy beyond oil. In an effort to attract more foreign investment and privatization of state-run companies, the government has greenlighted th of foreigners at the head of state-run companies [20,21]. Therefore, the CEO towards firm CSR disclosure policy in Saudi Arabia is an empirica most Saudi Arabian firms are family-owned or controlled by families [22, to [24], three Saudi families control more than 41% of executive board pos listed firms, and these families dominate the boards of 68 listed firms ou listed firms.…”
Section: Introductionmentioning
confidence: 99%
“…This means that organisations prioritise corporate governance are highly likely to perform better in the long run. Alregab (2023) empirically analysed the role of corporate governance in attracting foreign investment in Saudilisted firms in light of Vision 2030. The findings of the study showed that corporate governance positively correlates with foreign investment.…”
Section: Resultsmentioning
confidence: 99%
“…This approach will help prevent immoral actors from undermining the efforts of organisations to promote good governance. Good governance is crucial in attracting investors to an organisation, which, in turn, benefits the entire country (Alregab, 2023). Therefore, organisations must prioritise corporate governance to enhance their reputation, build trust with stakeholders, and contribute to the country's development and the business world.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally identified as the method of practicing good management, or more precisely, wise management [19]. Corporate governance is defined as "the set of laws, rules and standards that define the relationship between the company's management on the one hand, and shareholders, owners and stakeholders on the other hand" [20]. The objectives of corporate governance is to maximize firm performance by achieving economic efficiency and to develop systems that constrain the firm"s management within an ethical framework that is based on guarantees of accountability and transparency.…”
Section: Theoretical Framework Of Corporate Governance and Creative A...mentioning
confidence: 99%